2023
DOI: 10.1038/s41598-022-26872-x
|View full text |Cite
|
Sign up to set email alerts
|

Safeguarding pollinators requires specific habitat prescriptions and substantially more land area than suggested by current policy

Abstract: Habitat loss and fragmentation are major drivers of global pollinator declines, yet even after recent unprecedented periods of anthropogenic land-use intensification the amount of habitat needed to support insect pollinators remains unknown. Here we use comprehensive pan trap bee survey datasets from Ontario, Canada, to determine which habitat types are needed and at what spatial scales to support wild bee communities. Safeguarding wild bee communities in a Canadian landscape requires 11.6–16.7% land-cover fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Therefore, many of the pollinators in their study site could be wetland species that develop in wetlands and paddy fields, whereas many of the pollinators in Akana Wetland may originate from the surrounding environment. Pindar and Raine ( 2023 ) reported that wetland are important foraging habitats for bumblebees. Stephenson et al ( 2018 ) also reported that wetland-dependent bees were less abundant in small wetlands based on a multi-site pan trap survey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, many of the pollinators in their study site could be wetland species that develop in wetlands and paddy fields, whereas many of the pollinators in Akana Wetland may originate from the surrounding environment. Pindar and Raine ( 2023 ) reported that wetland are important foraging habitats for bumblebees. Stephenson et al ( 2018 ) also reported that wetland-dependent bees were less abundant in small wetlands based on a multi-site pan trap survey.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on wetland pollinators have often been focusing on bees and wasps (e.g. Bartholomew and Prowell 2006 ; Hall and Ascher 2010 ; Moroń et al 2008 ; Pascarella et al 2000 ; Pindar and Raine 2023 ; Purvis et al 2020 ; Stephenson et al 2018 ; Vickruck et al 2019 ), and studies covering pollinator communities of multiple taxa are still limited (but Kato and Miura 1996 ; Mahoro et al 2008 ; Negoro 2004 ; Nkurikiyimana et al 2023 ). However, the previous studies on pollinator communities indicate that flies often dominate as pollinators in wetlands (Kato and Miura 1996 ; Mahoro et al 2008 ), unlike in forests and grasslands where bees are more prevalent (Shinjo et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%